A hybrid model based on latest version of NCEP CFS coupled model for Indian monsoon rainfall forecast. (9th July 2014) - Pattanaik, D. R.; Kumar, Arun
Abstract The forecast skill of all India summer monsoon rainfall (AISMR) during June to September (JJAS) in the new version of the National Centers for Environmental Prediction (NCEP)'s Climate Forecast System version 2 (CFSv2) is analyzed by considering 28 years (1982–2009) retrospective forecasts. The spatial patterns of JJAS mean rainfall and its interannual variability is more realistic over the Indian monsoon region in CFSv2 as compared to previous version of NCEP's CFS. A hybrid (dynamical–empirical) model based on the forecast variables of CFSv2 is developed for AISMR, which shows correlation that is highly significant with observed AISMR. The hybrid model correctly predicted the observed AISMR departure of 2013.